In Vitro Shoot Bud Differentiation from Hypocotyl Explants of Chili Peppers (Capsicum annuum L.) - Owk ANIEL KUMAR; Sape SUBBA TATA (Notulae Scientia Biologicae, 2010)
Chili pepper (Capsicum annuum L.) is an economically important spice crop in tropical and subtropical countries. In vitro plant regeneration was obtained from 15th day old hypocotyl explants of three chili pepper cultivars (Capsicum annuum L., var. X-235, var. PC-1 and var. Pusa Jwala). Among the genotypes of Capsicum L. var. X-235 responded better than the var. PC-1 and var. Pusa Jwala. MS medium containing BAP (4.0 mg/l) and IAA (0.5 mg/l) was found to be the best medium for the production of maximum number of shoot buds in all the genotypes of chili pepper i.e., 6.800.16 (var. X-235), 5.000.19 (var. PC-1) and 4.800.12 (var. Pusa Jwala). The shoots were rooted on MS medium fortified with IBA (0.5 mg/l). Rooted plants were hardened and transplanted to the soil. The plants showed 80-90% survival during transplantation.